Silicon carbide porous ceramic with adjustable resistance and preparation method thereof
By adding SiO2 to the porous silicon carbide ceramics and performing a carbon-thermal reduction reaction, adjusting the stoichiometric ratio of Si and C elements, the problem of difficulty in controlling the resistance of silicon carbide porous ceramics is solved, and the controllability of the resistance within a specific range and the suitability of the porosity is achieved, meeting the electrical performance requirements of semiconductor equipment.
Patent Information
- Application Number
- CN202311805339.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-26
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-12-26
AI Technical Summary
The prior art is difficult to achieve adjustable and controllable resistance of silicon carbide porous ceramics while maintaining the ceramic material's communication channel, suitable pore size and porosity.
By adding SiO2 powder to the SiC raw material powder, a carbon-thermal reduction reaction occurs with the pore-forming agent cleavage product C during the high-temperature sintering process to generate SiC, reducing the residual C amount of the pore inner wall, and adjusting the stoichiometric ratio of Si and C elements, the surface resistance of silicon carbide porous ceramics is controlled.
The surface resistance of silicon carbide porous ceramics is controlled and adjustable in the range of 102-1012Ω and the porosity is within the range of 17-65%, meeting the demand for electrical performance in semiconductor equipment.
Smart Images

Figure CN117776728B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon carbide porous ceramic with adjustable resistance and a preparation method thereof, belonging to the field of inorganic non-metallic material preparation. Background Art
[0002] High-precision vacuum chuck is an important component for semiconductor equipment, mainly used for precise adsorption and transfer of semiconductor components such as LCD display screens and silicon wafers during processes such as lithography, detection and packaging. The function of vacuum adsorption is mainly achieved through porous ceramic materials, which have specific requirements for the pore size and porosity of the material. In addition, in order to prevent static electricity accumulation or static electricity dissipation, specific requirements are also put forward for the electrical properties of porous ceramic materials, requiring that their surface resistance should not be too high or too low, but within a certain range. Silicon carbide has the characteristics of high thermal conductivity, high mechanical strength, high stiffness, low thermal expansion coefficient, good thermal uniformity, corrosion resistance, wear resistance, etc., and is one of the preferred materials for high-precision vacuum chucks for semiconductor equipment. At present, there are many studies on the electrical properties of silicon carbide dense ceramics, but there are fewer studies on the electrical properties of silicon carbide porous ceramics for semiconductor equipment. Compared with dense ceramics, porous ceramics have different mechanisms for regulating electrical properties due to the presence of pores.
[0003] The patents related to the regulation of electrical properties of dense silicon carbide ceramics mainly include: China invention patent authorization announcement number: Silicon carbide / boron carbide / graphene ceramics disclosed in CN108911756A. Graphene is evenly dispersed in silicon carbide ceramics by utilizing the high conductivity of graphene materials, so that graphene is evenly distributed and coated with silicon carbide particles in the grain boundaries. Graphene can reduce the grain boundary resistance of silicon carbide ceramics, and at the same time, graphene forms a conductive network in the grain boundaries of silicon carbide ceramics, further reducing the resistivity of the ceramic as a whole. The conductivity is controlled by controlling the thickness of the coating layer on the surface of the silicon carbide particles by controlling the content of graphene. China invention patent authorization announcement number: Silicon carbide / graphite composite ceramics disclosed in CN106045520A. In this patent, phenolic resin is mainly used as a carbon source, and the performance of silicon carbide ceramics is adjusted by adding a graphite phase. However, when the amount of phenolic carbon source added is too high, the density of the ceramic will decrease, thereby affecting the mechanical properties of the material. At present, there is no public application for patents related to the regulation of electrical properties of silicon carbide porous ceramics. Summary of the invention
[0004] How to achieve adjustable and controllable preparation of silicon carbide porous ceramic resistors while maintaining interconnected pores, appropriate pore size and porosity in the ceramic material is a technical bottleneck in promoting the application of silicon carbide porous ceramic materials in semiconductor equipment, and is also a technical difficulty to be solved by the present invention.
[0005] In order to solve the technical difficulties of adjustable resistance of silicon carbide porous ceramics, the technical solution adopted by the present invention is: by adding SiO2 powder to the SiC raw material powder, it undergoes an in-situ carbon thermal reduction reaction with the pore-forming agent cracking product C during the high-temperature sintering process to generate SiC, thereby reducing the amount of residual C on the inner wall of the pores, and by adjusting the stoichiometric ratio of Si and C elements, the surface resistance of the silicon carbide porous ceramics can be regulated.
[0006] Specifically, on one hand, the present invention provides a silicon carbide porous ceramic with adjustable resistance, comprising: a silicon carbide main phase, a sintering aid phase and a connected pore phase; preferably, the sintering aid phase is a boron carbide phase.
[0007] Preferably, the content of the silicon carbide main phase is 44-88.9wt%, and the content of the sintering aid phase is 11.1-66wt%.
[0008] Preferably, the porosity of the silicon carbide porous ceramic is in the range of 17 to 65%.
[0009] Preferably, the surface resistance of the silicon carbide porous ceramic is 10 2 ~10 12 Ω.
[0010] In another aspect, the present invention provides a method for preparing a silicon carbide porous ceramic with adjustable resistance, comprising:
[0011] (1) mixing silicon carbide powder, a pore former, SiO2 powder, a sintering aid, a binder, a dispersant and a solvent to obtain a mixed slurry;
[0012] (2) spray granulating and sieving the obtained mixed slurry to obtain spherical composite powder;
[0013] (3) transferring the obtained spherical composite powder to a mold for pressing and molding to obtain a ceramic green body;
[0014] (4) The ceramic green body is subjected to cracking, carbon thermal reduction reaction and sintering to obtain the silicon carbide porous ceramic with adjustable resistance.
[0015] Preferably, in step (1):
[0016] The average particle size of the SiC powder is 1 to 10 μm;
[0017] The sintering aid is B4C powder, and the particle size of the B4C powder is 1 to 5 μm;
[0018] The particle size of the SiO2 powder is ≤5 μm;
[0019] The pore-forming agent is polymethyl methacrylate (PMMA) with a particle size of 1 to 8 μm;
[0020] The binder is at least one of polyvinyl alcohol (PVA), polyvinyl ketone (PVP), polyacrylic acid (PAA) and phenolic resin;
[0021] The dispersant is at least one of polyethylene glycol (PEG) and polyacrylic acid (PAA);
[0022] The solvent is at least one of anhydrous ethanol, acetone and water.
[0023] Preferably, in step (1): silicon carbide powder, pore former, SiO2 powder and sintering aid are used as composite powder, the total mass of the composite powder is 100%, the content of silicon carbide powder is 44-88.9wt%, the content of pore former is 10-40wt%, the content of SiO2 powder is 0-10wt%, and the content of sintering aid is 0.1-6wt%;
[0024] The amount of the adhesive added is 12-1wt% of the total mass of the composite powder, preferably 8wt%-11wt%;
[0025] The amount of the dispersant added is 1-4wt% of the total mass of the composite powder, preferably 2wt%;
[0026] The solid content of the composite powder in the mixed slurry is 30-46 wt %, preferably 38 wt %.
[0027] Preferably, in step (2): the parameters of the spray granulation include: a temperature of 60 to 120° C., an atomizer speed set at 120 to 200 rpm; and a particle size range of the spherical composite powder of 1 to 200 μm.
[0028] Preferably, in step (3): the pressing method is dry pressing or isostatic pressing, preferably dry pressing first and then isostatic pressing;
[0029] The dry pressing pressure is 20-50 MPa;
[0030] The isostatic pressing pressure is 150-200 MPa.
[0031] Preferably, in step (4): the cracking parameters include: under vacuum conditions, the cracking temperature is 650-1050° C., and the insulation time is 0.5-4 h;
[0032] The parameters of the carbon thermal reduction reaction include: a temperature of 1500 to 1600° C. and a holding time of 1 to 4 hours;
[0033] The sintering parameters include: sintering temperature of 1850-2100°C, holding time of 0.5-2h;
[0034] Preferably, the cracking, carbothermal reduction reaction and sintering are performed at one time in the same sintering furnace.
[0035] Beneficial effects:
[0036] The present invention provides a silicon carbide porous ceramic with adjustable resistance and a preparation method thereof, which solves the problem that the surface resistance performance of the silicon carbide porous ceramic required in the current semiconductor industrialization process cannot meet the application requirements. The obtained silicon carbide porous ceramic has different resistance performances in 10 2 ~10 12 The preparation can be controlled within the range of Ω, and the porosity is in the range of 17 to 65%. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The SEM photo and EDS scanning analysis results of the silicon carbide porous ceramic obtained in Example 1 (the scale bar is 5 μm);
[0038] Figure 2 The SEM image (scale 40 μm) and EDS scanning analysis result (scale 5 μm) of the silicon carbide porous ceramic obtained in Example 2;
[0039] Figure 3 This is a SEM photo of the silicon carbide porous ceramic obtained in Example 3 (scale 40 μm);
[0040] Figure 4 The EDS scanning analysis results of the silicon carbide porous ceramic obtained in Example 3 (scale 5 μm);
[0041] Figure 5 The SEM image (scale 40 μm) and EDS scanning analysis result (scale 5 μm) of the silicon carbide porous ceramic obtained in Example 4;
[0042] Figure 6 The SEM image (scale bar 40 μm) and EDS scanning analysis result (scale bar 5 μm) of the silicon carbide porous ceramic obtained in Example 5 are shown. DETAILED DESCRIPTION
[0043] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0044] In the present disclosure, during the preparation of silicon carbide porous ceramics, the pore-forming agent used (such as polymethyl methacrylate (PMMA) etc.) will gradually crack into C with strong reducing properties and be evenly distributed on the pore walls of the material. After adding SiO2, it can gradually react with the cracked C during the sintering process to generate a high-resistance SiC phase, and the newly generated SiC is a non-stoichiometric ratio. By adjusting the stoichiometric ratio of Si and C, the purpose of adjusting the resistance of silicon carbide porous ceramics can be achieved. As an improvement, the phase composition of the silicon carbide porous ceramics mainly includes a main phase-silicon carbide phase, a sintering aid phase-boron carbide and a connected pore phase. The porosity of the ceramic material is in the range of 17-65%, and the ceramic material can achieve a surface resistance of 10^2 to 10 12 Ω controllable and adjustable preparation.
[0045] The following is an exemplary description of the method for preparing the silicon carbide porous ceramic with adjustable resistance provided by the present invention.
[0046] Silicon carbide powder (44-88.9wt%), pore-forming agent (10-40wt%), SiO2 powder (0-10wt%), B4C powder (0.1-6wt%), adhesive, dispersant, etc. are mixed in a quantitative solvent (such as anhydrous ethanol, etc.), and a mixed slurry is obtained after ball milling. Sintering with the above components has the following advantages: the added SiO2 powder reacts with the C cracked by the pore-forming agent to produce SiC, which is consistent with the composition of the main phase and does not introduce other impurity elements; the newly generated SiC and the main phase can be sintered in an integrated manner, which is beneficial to the maintenance of the mechanical properties of silicon carbide porous ceramics. Phenolic resin is selected as a binder and polyethylene glycol (PEG) is selected as a dispersant and dissolved in an organic solvent to form a binder solute. The raw material powder and the binder are placed in a ball mill for ball milling and mixing treatment, wherein the diameter of the silicon carbide grinding ball is 5mm, and the ball milling is carried out at 300 rotations per minute for 4 hours, and the mixture is evenly mixed to form a mixed slurry. Preferably, the silicon carbide powder is β-SiC with an average particle size of 1 to 10 μm and a purity of ≥ 99.5%. The silicon carbide powder, pore former, sintering aid, etc. are uniformly mixed.
[0047] The mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder (or granulated powder), which is then sieved. The outlet temperature used for the spray granulation is 60-120° C. The granulated powder is then sieved, and the sieve used is 100 mesh.
[0048] The spherical composite powder is transferred to a mold and dry pressed or isostatically pressed to obtain a ceramic green body. The molding pressure of the dry pressing molding is 20-50 MPa, and the holding time is 0.5-5 minutes to ensure that the particles forming the green body are in close contact.
[0049] The ceramic blank is placed in a graphite crucible and heated and cracked under vacuum conditions (referred to as cracking) to obtain a porous structure blank. The thermal cracking temperature is 650-1050°C and the holding time is 0.5-4h. During the thermal cracking process, the furnace temperature rises to 650-1050°C and the holding time is 0.5-4h, so that the binder and pore former in the ceramic blank are completely cracked into C, and the pore former forms a connected pore structure. As an example, the obtained ceramic blank is placed in a mold for thermal cracking. The pore former (polymethyl methacrylate (PMMA)) will crack into a highly conductive phase C under high temperature conditions. The furnace temperature is raised to 650-1050°C at a heating rate of 3-10°C / min, and the holding time is 0.5-4h to obtain a porous structure blank of silicon carbide ceramics.
[0050] The porous structure blank is subjected to carbon thermal reduction reaction and high-temperature sintering under the protection of inert gas. Then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics with adjustable resistance. The carbon thermal reduction reaction temperature is 1500-1600°C and the holding time is 1-4h. The sintering temperature is 1850-2100°C and the holding time is 0.5-2h. During the high-temperature sintering process, an argon (Ar) protective atmosphere should be filled, and the sintering temperature should be set to two stages: (1) the carbon thermal reduction reaction temperature is 1500-1600°C and the holding time is 1-4h, so that the cracked C reacts with SiO2 to fully generate SiC, and the reaction equation is 2C+SiO2=SiC+CO2; (2) the sintering temperature is 1850-2100°C and the holding time is 0.5-2h, so that SiC is sintered and obtains better mechanical properties.
[0051] As an example, the silicon carbide ceramic preparation process includes the following steps:
[0052] Weighing → ball milling → granulation → molding → thermal cracking → sintering. The silicon carbide powder, pore-forming agent, SiO2 powder and B4C powder are weighed according to a weight ratio; then mixed with a binder, a dispersant and the like in a quantitative anhydrous ethanol solvent, and mixed by ball milling to obtain a mixed slurry; the obtained mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder, which is sieved; the obtained spherical composite powder is transferred to a mold, dry-pressed or isostatically pressed to obtain a ceramic blank; the ceramic blank is placed in a graphite crucible, heated and cracked under vacuum conditions, the thermal cracking temperature is 650-1050°C, and the insulation time is 0.5-4h; then a carbon thermal reduction reaction and high-temperature sintering are carried out under the protection of an inert gas, the carbon thermal reduction reaction temperature is 1500-1600°C, the insulation time is 1-4h, the sintering temperature is 1850-2100°C, the insulation time is 0.5-2h, and then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics with adjustable resistance.
[0053] In the present invention, the cracked C of the pore-forming agent (PMMA) used is mainly distributed on the pore wall of the interconnected pore structure, and as a low-resistance phase, the material will present a lower surface resistance. The carbon thermal reduction reaction of SiO2 with C under high temperature conditions can effectively reduce the residual C on the pore wall, significantly reduce the content of the low-resistance phase C, and thus increase the surface resistance of the material. By adjusting the content of each component in step 1, the stoichiometric ratio of Si and C elements in the carbon thermal reduction reaction product is regulated, thereby achieving the regulation of the surface resistance of the silicon carbide porous ceramic. The resistance of the obtained silicon carbide porous ceramic is tested by a surface resistance meter. The porosity of the obtained silicon carbide porous ceramic is tested by the Archimedean method.
[0054] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0055] Example 1
[0056] 83.28 g (69.4 wt%) of silicon carbide powder, 36.00 g (30 wt%) of PMMA pore former, 0.72 g (0.6 wt%) of B4C powder, 12 ml (phenolic resin) of adhesive, 1.8 ml (polyethylene glycol) of dispersant were mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry was obtained after ball milling. The solid content of the composite powder in the obtained mixed slurry was 38 wt%. The obtained mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder, which is sieved; the obtained spherical composite powder is transferred to a mold, dry-pressed or isostatically pressed to obtain a ceramic blank; the ceramic blank is placed in a graphite crucible, and heated and cracked under vacuum conditions, the thermal cracking temperature is 900°C, and the insulation time is 2h; then, a carbon thermal reduction reaction and high-temperature sintering are carried out under the protection of an inert gas, the carbon thermal reduction reaction temperature is 1600°C, the insulation time is 2h, the sintering temperature is 1950°C, the insulation time is 0.5h, and then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics.
[0057] Example 2
[0058] 79.68g (66.4wt%) of silicon carbide powder, 36.00g (30wt%) of PMMA pore former, 3.60g (3wt%) of SiO2 powder, 0.72g (0.6wt%) of B4C powder, 12ml (phenolic resin) of adhesive, 1.8ml (polyethylene glycol) of dispersant are mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry is obtained after ball milling. The solid content of the composite powder in the obtained mixed slurry is 38wt%. The obtained mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder, which is sieved; the obtained spherical composite powder is transferred to a mold, dry-pressed or isostatically pressed to obtain a ceramic blank; the ceramic blank is placed in a graphite crucible, and heated and cracked under vacuum conditions, the thermal cracking temperature is 900°C, and the insulation time is 2h; then, a carbon thermal reduction reaction and high-temperature sintering are carried out under the protection of an inert gas, the carbon thermal reduction reaction temperature is 1600°C, the insulation time is 2h, the sintering temperature is 1950°C, the insulation time is 0.5h, and then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics.
[0059] Example 3
[0060] 70.80 g (59 wt%) of silicon carbide powder, 36.00 g (30 wt%) of PMMA pore former, 6.00 g (5 wt%) of SiO2 powder, 7.20 g (6 wt%) of B4C powder, 12 ml (phenolic resin) of adhesive, 1.8 ml (polyethylene glycol) of dispersant were mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry was obtained after ball milling. The solid content of the composite powder in the obtained mixed slurry was 38 wt%. The obtained mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder, which is sieved; the obtained spherical composite powder is transferred to a mold, dry-pressed or isostatically pressed to obtain a ceramic blank; the ceramic blank is placed in a graphite crucible, and heated and cracked under vacuum conditions, the thermal cracking temperature is 900°C, and the insulation time is 2h; then, a carbon thermal reduction reaction and high-temperature sintering are carried out under the protection of an inert gas, the carbon thermal reduction reaction temperature is 1600°C, the insulation time is 2h, the sintering temperature is 1950°C, the insulation time is 0.5h, and then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics.
[0061] Example 4
[0062] 106.68g (88.9wt%) of silicon carbide powder, 12.00g (10wt%) of PMMA pore former, 1.20g (1wt%) of SiO2 powder, 0.12g (0.1wt%) of B4C powder, 12ml (phenolic resin) of adhesive, 1.8ml (polyethylene glycol) of dispersant are mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry is obtained after ball milling. The solid content of the composite powder in the obtained mixed slurry is 38wt%. The obtained mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder, which is sieved; the obtained spherical composite powder is transferred to a mold, dry-pressed or isostatically pressed to obtain a ceramic blank; the ceramic blank is placed in a graphite crucible, and heated and cracked under vacuum conditions, the thermal cracking temperature is 900°C, and the insulation time is 2h; then, a carbon thermal reduction reaction and high-temperature sintering are carried out under the protection of an inert gas, the carbon thermal reduction reaction temperature is 1600°C, the insulation time is 2h, the sintering temperature is 1950°C, the insulation time is 0.5h, and then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics.
[0063] Example 5
[0064] 52.80 g (44 wt%) of silicon carbide powder, 48.00 g (40 wt%) of PMMA pore former, 12.00 g (10 wt%) of SiO2 powder, 7.20 g (6 wt%) of B4C powder, 12 ml (phenolic resin) of adhesive, 1.8 ml (polyethylene glycol) of dispersant were mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry was obtained after ball milling. The solid content of the composite powder in the obtained mixed slurry was 38 wt%. The obtained mixed slurry is subjected to a spray granulation process to obtain a spherical composite powder, which is sieved; the obtained spherical composite powder is transferred to a mold, dry-pressed or isostatically pressed to obtain a ceramic blank; the ceramic blank is placed in a graphite crucible, and heated and cracked under vacuum conditions, the thermal cracking temperature is 900°C, and the insulation time is 2h; then, a carbon thermal reduction reaction and high-temperature sintering are carried out under the protection of an inert gas, the carbon thermal reduction reaction temperature is 1600°C, the insulation time is 2h, the sintering temperature is 1950°C, the insulation time is 0.5h, and then the temperature is lowered to room temperature to obtain silicon carbide porous ceramics.
[0065] Example 6
[0066] The preparation process of silicon carbide porous ceramics in this Example 6 refers to Example 2, with the only difference being: 82.08g (68.4wt%) of silicon carbide powder, 36.00g (30wt%) of PMMA pore former, 1.20g (1wt%) of SiO2 powder, 0.72g (0.6wt%) of B4C powder, 12ml (phenolic resin) of adhesive, 1.8ml (polyethylene glycol) of dispersant, etc. are mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry is obtained after ball milling.
[0067] Example 7
[0068] The preparation process of silicon carbide porous ceramics in this Example 7 refers to Example 2, with the only difference being: 77.28 g (64.4 wt%) of silicon carbide powder, 36.00 g (30 wt%) of PMMA pore former, 6.00 g (5 wt%) of SiO2 powder, 0.72 g (0.6 wt%) of B4C powder, 12 ml (phenolic resin) of adhesive, 1.8 ml (polyethylene glycol) of dispersant, etc. are mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry is obtained after ball milling.
[0069] Example 8
[0070] The preparation process of silicon carbide porous ceramics in this Example 8 refers to Example 2, with the only difference being: 71.28 g (59.4 wt%) of silicon carbide powder, 36.00 g (30 wt%) of PMMA pore former, 12.00 g (10 wt%) of SiO2 powder, 0.72 g (0.6 wt%) of B4C powder, 12 ml (phenolic resin) of adhesive, 1.8 ml (polyethylene glycol) of dispersant, etc. are mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry is obtained after ball milling.
[0071] Comparative Example 1
[0072] The preparation process of silicon carbide porous ceramics in this comparative example 1 refers to Example 2, with the only difference being: 67.68g (56.4wt%) of silicon carbide powder, 36.00g (30wt%) of PMMA pore former, 15.6g (13wt%) of SiO2 powder, 0.72g (0.6wt%) of B4C powder, 12ml (phenolic resin) of adhesive, 1.8ml (polyethylene glycol) of dispersant, etc. are mixed in a quantitative anhydrous ethanol solvent, and a mixed slurry is obtained after ball milling.
[0073] Figure 1 The SEM photograph and EDS scanning analysis results of Example 1 show that the pore-forming agent (PMMA) forms interconnected channels after high-temperature pyrolysis. The EDS point analysis results in the channels show that the C, Si, and O elements account for 85.1wt%, 13.62wt%, and 1.28wt%, respectively, indicating that the channels are mainly residual C. The EDS surface analysis results show that the residual C is distributed through the channels, and grains and grain boundaries can be observed in the SiC matrix.
[0074] Figure 2The SEM photo and EDS scanning analysis results of Example 2 show that the mass fractions of C, Si, and O are 59.74%, 8.49%, and 31.77%, and the atomic ratios are 74.96%, 8.00%, and 17.05% respectively. There is a higher proportion of residual C in the pores, but the carbon content is lower than that in Example 1, indicating that after 3wt% of SiO2 is added, SiO2 can consume the proportion of carbon cracked in the high temperature environment in the high temperature sintering environment. It can be observed that the ceramic is in a good sintering state and presents a coherent whole.
[0075] Figure 3 is the SEM photo of Example 3, Figure 4 The EDS scanning analysis results of Example 3 show that the mass fractions of C, Si, and O are 36.34%, 58.54%, and 5.12%, and the atomic ratios are 55.72%, 38.38%, and 5.89% respectively. There is a higher proportion of residual C in the pores, but the carbon content is lower than that of Example 2, indicating that after adding 5wt% SiO2, SiO2 can consume the carbon cracked in the high temperature environment in the high temperature sintering environment. It can be seen that there are protruding grains, and the grains are still connected as one.
[0076] Figure 5 The SEM photo and EDS scanning analysis results of Example 4 show that the mass fractions of C, Si, and O are 45.84%, 44.08%, and 10.08%, and the atomic ratios are 63.44%, 26.09%, and 10.47% respectively. There is a higher proportion of residual C in the pores, but the carbon content is lower than that of Example 3, indicating that after adding 1wt% SiO2, how much Si is consumed can be judged based on the content of residual O. Analysis shows that after sintering, it is mainly carbon cracked by polymethyl methacrylate (PMMA) under high temperature conditions.
[0077] Figure 6 The SEM photo and EDS scanning analysis results of Example 5 show that the mass fractions of C, Si and O are 39.83%, 53.47% and 6.70% respectively, and the atomic ratios are 58.81%, 33.77% and 7.42% respectively. There is a higher proportion of residual C in the pores, but the carbon content is lower than that in Example 4, indicating that after adding 10wt% of SiO2, the SiC particles cannot fully diffuse at the sintering temperature, and they appear as separate small particles under the electron microscope. When the current flows through the particle surface, the high Si content can improve the resistance of the material.
[0078] Table 1 shows the performance parameters of silicon carbide porous ceramics prepared by the present invention:
[0079]
[0080]
Claims
1. A method for preparing silicon carbide porous ceramics with adjustable resistance, characterized in that: The silicon carbide porous ceramic with adjustable resistance comprises: a silicon carbide main phase, a sintering aid phase and a connected pore phase; The preparation method comprises: (1) mixing silicon carbide powder, a pore former, SiO2 powder, a sintering aid, a binder, a dispersant and a solvent to obtain a mixed slurry; Silicon carbide powder, pore former, SiO2 powder and sintering aid are used as composite powder, the total mass of the composite powder is 100%, the content of silicon carbide powder is 44-88.9wt%, the content of pore former is 10-40wt%, the content of SiO2 powder is 0-10wt%, and the content of sintering aid is 0.1-6wt%; (2) spray granulating and sieving the obtained mixed slurry to obtain spherical composite powder; (3) transferring the obtained spherical composite powder into a mold for pressing to obtain a ceramic green body; (4) The ceramic green body is subjected to cracking, carbon thermal reduction reaction and sintering to obtain the silicon carbide porous ceramic with adjustable resistance.
2. The preparation method according to claim 1, characterized in that: In the silicon carbide porous ceramic with adjustable resistance, the sintering aid phase is a boron carbide phase.
3. The preparation method according to claim 1, characterized in that: In the silicon carbide porous ceramic with adjustable resistance, the content of the silicon carbide main phase is 44-88.9wt%, and the content of the sintering aid phase is 11.1-66wt%.
4. The preparation method according to claim 1, characterized in that: The porosity of the silicon carbide porous ceramic with adjustable resistance is in the range of 17-65%.
5. The preparation method according to claim 1, characterized in that: The surface resistance of the silicon carbide porous ceramic with adjustable resistance is 10 2 ~10 12 Ω.
6. The preparation method according to claim 1, characterized in that: In step (1): The average particle size of the SiC powder is 1 to 10 μm; The sintering aid is B4C powder, and the particle size of the B4C powder is 1 to 5 μm; The particle size of the SiO2 powder is ≤5 μm; The pore-forming agent is polymethyl methacrylate, and the particle size is 1 to 8 μm; The binder is at least one of polyvinyl alcohol, polyvinyl ketone, polyacrylic acid and phenolic resin; The dispersant is at least one of polyethylene glycol and polyacrylic acid; The solvent is at least one of anhydrous ethanol, acetone and water.
7. The preparation method according to claim 1, characterized in that: In step (1), The amount of the adhesive added is 1 to 12 wt % of the total mass of the composite powder; The amount of the dispersant added is 1 to 4 wt% of the total mass of the composite powder; The solid content of the composite powder in the mixed slurry is 30-46 wt %.
8. The preparation method according to claim 7, characterized in that: In step (1), The amount of the adhesive added is 11wt% of the total mass of the composite powder; The amount of the dispersant added is 2wt% of the total mass of the composite powder; The solid content of the composite powder in the mixed slurry is 38 wt %.
9. The preparation method according to claim 1, characterized in that: In step (2), the parameters of the spray granulation include: a temperature of 60 to 120° C., an atomizer speed of 120 to 200 rpm; and a particle size range of the spherical composite powder of 1 to 200 μm.
10. The preparation method according to claim 1, characterized in that: In step (3): the pressing method is dry pressing and / or isostatic pressing; The dry pressing pressure is 20-50 MPa; The isostatic pressing pressure is 150-200 MPa.
11. The preparation method according to claim 10, characterized in that: The compression molding method is dry compression molding first, and then isostatic compression molding.
12. The preparation method according to claim 1, characterized in that: In step (4), the cracking parameters include: under vacuum conditions, the cracking temperature is 650-1050° C., and the insulation time is 0.5-4 h; The parameters of the carbon thermal reduction reaction include: a temperature of 1500 to 1600° C. and a holding time of 1 to 4 hours; The sintering parameters include: a sintering temperature of 1850-2100° C. and a heat preservation time of 0.5-2 h.
13. The preparation method according to claim 12, characterized in that: The cracking, carbothermal reduction reaction and sintering are carried out at one time in the same sintering furnace.
Citation Information
Patent Citations
Low-resistivity linear-resistance silicon carbide and graphite composite and preparation method thereof
CN106045520A
Silicon carbide ceramic with adjustable resistance and preparation method thereof
CN108911756A
Resistivity-controllable conductive silicon carbide foam ceramic material and its preparing process
CN1962544A